2009
DOI: 10.1002/gps.2344
|View full text |Cite
|
Sign up to set email alerts
|

APOE epsilon‐4 allele and cytokine production in Alzheimer's disease

Abstract: These preliminary findings suggest the involvement of inflammatory response in the pathogenic effect of the APOE epsilon-4 allele in AD, although their replication in larger samples is mandatory. The modest correlations between pro-inflammatory cytokines released at peripheral level and AD features emphasizes the need for further research to elucidate the role of neuroinflammation in pathophysiology of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 51 publications
0
18
1
1
Order By: Relevance
“…Animal models have shown the influence of APOE alleles on proinflammatory cytokine (TNF-alpha; IL-6; IL-1) expression and sepsis [154156]. Recently, we have reported an association between APOE alleles and IL-1beta levels in patients with AD [157]. Apolipoprotein E has a protective effect against apoptosis which is significantly reduced in the presence of the pathogenic epsilon 4 isoform [158].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have shown the influence of APOE alleles on proinflammatory cytokine (TNF-alpha; IL-6; IL-1) expression and sepsis [154156]. Recently, we have reported an association between APOE alleles and IL-1beta levels in patients with AD [157]. Apolipoprotein E has a protective effect against apoptosis which is significantly reduced in the presence of the pathogenic epsilon 4 isoform [158].…”
Section: Discussionmentioning
confidence: 99%
“…Among AD patients, those with the apoE4 allele had greater baseline and stimulated levels of IL-1β (Olgiati et al, 2010). ApoE co-localizes with microglia around Aβ plaques (Liu et al, 2013), and apoE4 mice have greater microgliosis and astrogliosis in response to Aβ than do apoE3 mice (Belinson and Michaelson, 2009).…”
Section: Mechanisms Underlying Sex Differences In Obesity and Alzhmentioning
confidence: 99%
“…It is important to underscore, however, that additional cross-sectional studies report no significant correlations between inflammation and MMSE (Olgiati et al, 2010; Ozturk et al, 2007; Popp et al, 2009), positive correlations (Kim et al, 2008; Sala et al, 2003), or report associations only with specific cytokines (e.g., IL-1 levels, but not TNF-α) (Tarkowski et al, 2003). For example, Sala et al (2003) reported a positive relationship between MMSE and three pro-inflammatory markers, including IL-1, IL-6, and TNF-α, and interpreted these findings as preliminary evidence for downregulation of inflammation in late clinical stages of the disease.…”
Section: Inflammation and Neurodegenerative Diseasementioning
confidence: 99%
“…While isolated reports indicate a negative correlation between inflammatory mediators and episodic memory (Forlenza et al, 2009), there is a dearth of information regarding how inflammation might associate or interact with particular cognitive domains in AD. Recent studies have addressed other neurobehavioral correlates of inflammation, and reported significant associations between cytokine levels and neuropsychiatric symptoms (Olgiati et al, 2010; Ozturk et al, 2007); in particular, TNF-α levels have been shown to positively correlate with symptoms associated with sickness behavior (Holmes et al, 2011), including depression, anxiety, agitation, and apathy on the Neuropsychiatric Inventory (NPI) in Alzheimer’s disease. However, there continues to be a lack of specificity in the literature regarding how and to what degree inflammation relates to specific cognitive and neurobehavioral processes.…”
Section: Inflammation and Neurodegenerative Diseasementioning
confidence: 99%